The Role of ChatGPT in Enhancing Students’ Critical Thinking in Academic Writing - Durratul Hikmah; Badilatil Walida (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
In recent years, there has been a significant shift in how students complete their assignments. This change is largely influenced by technological advancements, particularly the emergence of ChatGPT. Students have increasingly relied on ChatGPT for various aspects of their writing. This research aims to explore the role of ChatGPT in helping students develop their critical thinking skills in writing academic papers. The research employs a quantitative method with a survey technique. The subjects of this study are 40 English Education students on one of universities in East Java, representing Writing classes from each semester. In this study, questionnaires are used to determine the frequency of responses and the percentage size. The research identifies various roles that ChatGPT plays in students' critical thinking processes during academic writing, such as helping to identify text genres, assisting in evaluating the quality of writing and identifying the strengths and weaknesses of texts, as well as helping to generate new ideas for writing.